The Force Parameters of Inter Layers Shear under Lateral Pressure Action when Dispersed Materials Undergo Compacting - V.G. Barsukov; B. Krupicz; V.V. Barsukov (Механика машин, механизмов и материалов, 2014)
Method for calculation ultimate value of residual lateral pressure taking into account interparticulate friction effect when dispersed materials undergo compacting by criteria of interlayer shear and surface cracking is developed. Variation range of this pressure depending on cohesion strength of materials and interparticulate friction is determinate.